Forms of ideological hegemony: The example of “informal labour” and the case of Greece - Vaxevanoglou, Aliki (The Greek Review of Social Research, 2025)
Widely used in the social sciences, the concept of “informal labour” affects our perception of the social world. But is it a neutral and impartial concept? This study draws on extensive and unexploited archives of the International Labour Organization that established the concept of “informal labour”; it outlines the broader historical context of the concept's genesis, the process of its diffusion and highlights the main ideological obsession of the time: the imperative of economic development through massive industrialization. Focusing on the case of Greece, from the beginning of the 20th century until the 1980s, the study constantly contrasts the factual data and their ideological interpretation. The concept of “informal labour” is considered as a key indicator for approaching the complex phenomenon called ideological hegemony.